Design, Simulation and Hardware Implementation of a Multi Device Interleaved Boost Converter for Fuel Cell Applications - R. Seyezhai (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
This paper presents the analysis and implementation of a two-phase  Multi Device Interleaved  Boost Converter (MDIBC).  Among the various DC-DC  topologies, Multi device Interleaved converter is considered as a better solution for fuel cell  hybrid vehicles as it reduces the  input current ripple,  output voltage ripple and the size of passive components. Detailed analysis has been done to investigate the benefits of Multi device Interleaved boost converter by comparing  it with the conventional   Interleaved boost converter topology. Moreover, in this paper, power loss analysis (switching loss, conduction loss, inductor loss) of the proposed converter has been performed. Simulation study of Multi device interleaved converter has been studied using MATLAB/SIMULINK. Hardware prototype is built to validate the results.DOI: http://dx.doi.org/10.11591/ijpeds.v4i3.5883